Need Satisfaction as a Mediator of Associations between Interparental Relationship Dimensions and Autonomy Supportive Parenting: A Weekly Diary Study - Koçak, Aylin; Mouratidis, Athanasios; Uçanok, Zehra; Selcuk, Emre; Davies, Patrick T. (Family Process, 2020)
Guided by the self-determination theory, this weekly diary study tested a process model in which week-to-week mother-reported interparental conflict and perceived partner responsiveness were associated with maternal autonomy support by means of maternal psychological need satisfaction. During six consecutive weeks, 258 mothers (Mage = 41.71 years) and their 157 adolescents (51.4% females, Mage = 14.92 years) from Turkey provided weekly reports of the study variables via an online survey. Multilevel analyses showed that maternal need satisfaction was predicted by lower levels of interparental conflict and greater levels of perceived partner responsiveness. Maternal need satisfaction, in turn, was positively associated with maternal and adolescent reports of maternal autonomy support. Further, these week-to-week associations were partly moderated by maternal perfectionism. The results underscore the dynamic nature of the intra-family relationships, the important role of particular conditions in which mothers may become more autonomy supportive, and the necessity to consider mother’s personal characteristics while examining these dynamics.